Food Safety for the Holiday Season - Soohyoun Ahn; Keith R. Schneider (EDIS, 2014)
Food is always an important part of holiday festivities, but holiday meals can take a turn for the worse if food safety is not properly practiced when preparing and cooking the food. The food you serve your family and friends can be very harmful if your turkey, ham, or home-prepared meat products are not appropriately handled. The good news is that by practicing four basic food safety measures you can help prevent foodborne illness over the holiday season. This 6-page fact sheet provides information about safe food practices for the holidays. Written by Soohyoun Ahn and Keith R. Schneider, and published by the UF Department of Food Science and Human Nutrition, December 2014. (Photo: Stockbyte/Thinkstock)